Study of outcomes in patients with conserved blunt liver and splenic injuries - Meshram, Prashant (International Surgery Journal, 2019)
Background: Blunt abdominal injuries in the modern day are common due to vehicular accidents. Young males are more commonly involved and liver and spleen are the commonest organs injured. During the last century, the management of blunt force trauma has changed from observation and expectant management in the early part of the 1900s to operative intervention for all injuries, to the current practice of selective operative and nonoperative management. Methods: We studied outcomes of conservatively managed liver and splenic injuries in 51 patients who presented to a tertiary referral center over a period of 1 year. Patient demographics and outcomes were studied. Results: Males in the age group of 16-30 years were commonly involved. Liver was the commonest organ injured. Both liver and spleen were injured together only in 3 patients. One patient of liver injury was subjected to delayed surgery and 2 patients of splenic injury failed conservative management. Thus, the success rate of conservative management of blunt liver injuries was 96.87% and in splenic injuries was 90.91%. Conclusions: Outcome of conservative management of blunt liver and splenic injuries is extremely good, especially in patients who maintained hemodynamic stability. Nonoperative management of blunt liver splenic injuries should be the treatment modality of choice in hemodynamically stable patients with any grades of injuries.